Efficacy and safety of copanlisib in relapsed/refractory B-cell non-Hodgkin lymphoma: A meta-analysis of prospective clinical trials - Wang, Jinjin; Zhou, Hui; Mu, Mingchun; Zhao, Ailin; Cai, Zhaolun; Li, Linfeng; Wang, Mengyao; Niu, Ting (Frontiers in Immunology, 2022)
Background: Copanlisib is an intravenously administered pan-class I PI3K inhibitor, which has been demonstrated to have appreciable effects in the treatment of patients with lymphoma. The purpose of this meta-analysis was to evaluate the efficacy and safety of copanlisb in patients with relapsed/refractory (R/R) B-cell non-Hodgkin lymphoma (B-NHL). Methods: Original studies were searched by Pubmed, Web of science, Embase, and Cochrane Central Register of Controlled Trials before July 2022. Efficacy evaluation included complete response rate (CR), partial response rate (PR), rate of stable disease (SDR), ORR, disease control rate (DCR), rate of progressive disease (PDR), median progression-free survival (PFS), and median overall survival (OS). Any grade adverse reactions (AEs) and grade≥ 3 AEs were synthesized to assess safety. Results: Eight studies with a total of 652 patients with R/R B-NHL were identified. Of all articles, the pooled CR, PR, ORR, SDR, DCR and PDR were 13%, 40%, 57%, 19%, 86%, and 9%, correspondingly. The CR and ORR of combination therapy with rituximab were higher than that of copanlisib monotherapy for R/R B-NHL (34% vs 6%, p<0.01; 89% vs 42%, p<0.01). For patients with R/R indolent B-NHL, CR and ORR were lower in copanlisib monotherapy than in combination therapy with rituximab (7% vs 34%, p<0.01; 58% vs 92%, p<0.01). In all included studies, the pooled risk of any grade and grade≥ 3 AEs were 100% and 89%. The common any grade AEs included hyperglycemia (66.75%), hypertension (48.57%), diarrhea (35.06%), nausea (34.98%) and fatigue (30.33%). The common grade≥ 3 AEs involved hyperglycemia (45.14%), hypertension (35.07%), and neutropenia (14.75%). The comparison of AEs between the copanlisib monotherapy and the combination therapy with rituximab showed that hyperglycemia of any grade (p<0.0001), hypertension of any grade (p=0.0368), fatigue of any grade (p<0.0001), grade≥ 3 hypertension (p<0.0001) and grade≥ 3 hyperglycemia (p=0.0074) were significant differences between the two groups. Conclusion: Our meta-analysis demonstrated that the efficacy of both copanlisib monotherapy and combination therapy with rituximab in patients with R/R B-NHL were satisfactory, while treatment-related AEs were tolerable. Compared with copanlisib monotherapy, combination therapy with rituximab showed superior efficacy in R/R B-NHL, and its safety was manageable.